Literature Review: Peran Selenium dan Zink dalam Proses Penyembuhan Gastroenteritis Akut (GEA) pada Anak - Warda Eka Islamiah; Siti Rahayu Nadhiroh (Universitas Airlangga, 2023)
Background: Gastroenteritis often attacks toddlers and children because their immune systems are still weak, so they can be exposed to bacteria that cause diarrhea such as continuous vomiting which will increase dehydration (lack of fluids). Gastroenteritis is often accompanied by dehydration, either moderate to severe dehydration. Acute gastroenteritis is one of the leading causes of child mortality in the world. The results of several studies found that the administration of zinc and selenium supplements can shorten the healing time or the duration of hospitalization of patients with acute gastroenteritis. Objectives: The purpose of this literature review is to examine and analyze the role of selenium and zinc in the treatment of acute gastroenteritis in children. Methods: Using the literature review method by reviewing 10 journal articles with 8 articles discussing the role of zinc in the healing process of acute gastroenteritis in children and 2 articles discussing the role of selenium in the healing process of acute gastroenteritis in children. Discussion: The results showed that selenium contains enzymes that can reduce oxidative stress so that it plays a role in the healing process of acute diarrhea. Meanwhile, zinc can help the healing process because it increases the absorption of fluids from the intestine, helps the cleansing of the organism, and supports the regeneration and integrity of the mucosa, and has immune-related mechanisms. Conclusion: The administration of zinc and selenium can accelerate the healing of gastroenteritis in children.